2017
DOI: 10.1097/jcp.0000000000000766
|View full text |Cite
|
Sign up to set email alerts
|

Combination Antipsychotic Therapies

Abstract: Background Antipsychotic combinations (CA) are prescribed in schizophrenia despite limited evidence of efficacy. To explore the effect of switching from CA to monotherapy, we performed an exploratory analysis of the PROACTIVE study data, in which 305 patients with schizophrenia and schizoaffective disorder were followed for 30-months after randomization to long-acting-injectable (LAI) risperidone or oral 2nd-generation antipsychotic (OA). Methods Patients who entered the PROACTIVE study on CA (n=50), LAI (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…The mean size for all included studies was 4338.1067, and range of studies sizes were 22 to 70 969. These studies included 16 randomized controlled trials (Alphs et al 2016;Bai et al 2007; Barnett et al 2012;Bartzokis et al 2012;Bozzatello et al 2019;Buckley et al 2015;Detke et al 2014;Green et al 2015;Keks et al 2007;Leatherman et al 2014;Macfadden et al 2010;Malla et al 2016;Rosenheck et al 2011;Subotnik et al 2015;Weiden et al 2009Weiden et al , 2012, 11 prospective cohort studies (Aykut 2019;Bellido et al 2008;Conley et al 2003;Devito et al 1978;Joshi et al 2018b;Kim et al 2008;Moore et al 1998;Olivares et al 2009;San et al 2013;Schreiner et al 2014;Tavcar et al 2000), and 48 retrospective cohort studies (Anderson et al 2017;Ascher-Svanum et al 2013;Barrio et al 2013;Baser et al 2015;Bitter et al 2013;Chan et al 2015;Emsley et al 2008;Fan et al 2018;Foster et al 2017;Greene et al 2018;Grimaldi-Bensouda et al 2012;Haro et al 2007;…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean size for all included studies was 4338.1067, and range of studies sizes were 22 to 70 969. These studies included 16 randomized controlled trials (Alphs et al 2016;Bai et al 2007; Barnett et al 2012;Bartzokis et al 2012;Bozzatello et al 2019;Buckley et al 2015;Detke et al 2014;Green et al 2015;Keks et al 2007;Leatherman et al 2014;Macfadden et al 2010;Malla et al 2016;Rosenheck et al 2011;Subotnik et al 2015;Weiden et al 2009Weiden et al , 2012, 11 prospective cohort studies (Aykut 2019;Bellido et al 2008;Conley et al 2003;Devito et al 1978;Joshi et al 2018b;Kim et al 2008;Moore et al 1998;Olivares et al 2009;San et al 2013;Schreiner et al 2014;Tavcar et al 2000), and 48 retrospective cohort studies (Anderson et al 2017;Ascher-Svanum et al 2013;Barrio et al 2013;Baser et al 2015;Bitter et al 2013;Chan et al 2015;Emsley et al 2008;Fan et al 2018;Foster et al 2017;Greene et al 2018;Grimaldi-Bensouda et al 2012;Haro et al 2007;…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Eighteen Seventeen articles (Anderson et al 2017;Aykut 2019;Bai et al 2007;Barnett et al 2012;Barrio et al 2013;Bellido et al 2008;Bozzatello et al 2019;Emsley et al 2008;Foster et al 2017;Joshi et al 2018b;Keks et al 2007;Macfadden et al 2010;Malla et al 2016;Petri c et al 2019;Remington & Khramov 2001;Schreiner et al 2014 Tavcar et al 2000;Tiihonen et al 2011;Tomko et al 2016;Valevski et al 2012;Varner et al 2001;Xiao et al 2015Xiao et al , 2016Young-Xu et al 2016) assessed the number and rates of rehospitalizations and days spent in the hospital among patients taking LAIs compared with orals (Table 3). Of these studies, 27 reported that LAI users had statistically significantly lower mean number of rehospitalizations (Baser et al 2015;Bellido et al 2008;Detke et al 2014;Devito et al 1978;Grimaldi-Bensouda et al 2012;Haro et al 2007; Outpatient/emergency department visits Twenty-one studies (Baser et al 2015;Chan et al 2015;Fan et al 2018;Joshi et al 2018aJoshi et al , 2018bJoshi et al , 2018cLafeuille et al 2013…”
Section: Symptom Remission/relapsementioning
confidence: 99%
“…Ранее уже было показано, что комбинации антипсихотических препаратов повышают риск развития акатизии [12]; так, сочетание разных ААП было связано Таблица 1. Клинико-динамические показатели в группах исследования [19]. Кроме того, не было обнаружено различий в актуальном психическом состоянии пациентов с акатизией и без акатизии, они имели сопоставимые баллы по PANSS, что бы позволило объяснить назначение комбинированной терапии.…”
Section: Discussionunclassified